Comparative Study of Truck and Train Transportation Effects on Postharvest Quality and Physical Damage of Mangosteens - Ongkunaruk, Pornthipa; Supapvanich, Suriyan; Youryon, Pannipa; Sinthusamran, Sirima; Sanguansak, Nattaporn; Sitthiprasert, Wasetthee; Da, Li; Techavuthiporn, Chairat (My University, 2026)
Transportation is a major contributor to postharvest losses in mangosteens. This study compared the quality of mangosteens transported by train and by truck from an orchard in Chumphon Province to Bangkok and monitored poststorage changes at 25 ± 1°C and 64 ± 3% relative humidity (RH). During transit, truck shipments experienced internal conditions ranging from 26.0 to 33.0°C, 70.0 to 93.7% RH, and 9.5 to 105.4 m s−2 in vibration intensity, whereas train shipments ranged from 28.2 to 40.3°C, 40.8 to 96.8% RH, and 1.1 to 13.3 m s−2. Mangosteens transported by truck exhibited considerably higher physical damage (24.9 ± 10.51%) than those transported by train (2.9 ± 1.98%). During subsequent storage, truck-delivered fruit showed faster peel color development and more pronounced internal deterioration. Moreover, truck transport led to markedly greater increases in peel hardness and lignin content over time, while both transport modes produced negligible effects on total soluble solids (TSS) and titratable acidity (TA). In truck-delivered fruit, peel hardness was positively correlated with lignin content but negatively correlated with TSS and TA—relationships not observed in train-delivered samples. Statistical analyses, including analysis of variance, Pearson correlation, and principal component analysis, confirmed that transportation mode and storage duration significantly influenced mangosteen quality deterioration, with truck transport accelerating pericarp hardening and ripening. These findings highlight the importance of optimizing logistics, particularly by favoring rail transport, which produces a lower vibration threshold than truck delivery, thereby reducing physical damage and maintaining mangosteen quality throughout the supply chain.
Keywords: fruit quality; Garcinia mangostana L.; pericarp hardening; postharvest logistics